2008
DOI: 10.1007/s10661-008-0331-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contaminants in freshwater fish and their risk to piscivorous wildlife based on a national monitoring program

Abstract: Organochlorine chemical residues and elemental concentrations were measured in piscivorous and benthivorous fish at 111 sites from large U.S. river basins. Potential contaminant sources such as urban and agricultural runoff, industrial discharges, mine drainage, and irrigation varied among the sampling sites. Our objectives were to provide summary statistics for chemical contaminants and to determine if contaminant concentrations in the fish were a risk to wildlife that forage at these sites. Concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 75 publications
2
37
1
Order By: Relevance
“…The term 'currently used pesticide' used here means pesticides which are not subject to worldwide restrictions. These CUPs attract our interest because of their continued high production volume and occurrence in aquatic biota, [10][11][12] osprey eggs, [13] human breast milk [14] and Arctic media (e.g. air, water and ice).…”
Section: Introductionmentioning
confidence: 99%
“…The term 'currently used pesticide' used here means pesticides which are not subject to worldwide restrictions. These CUPs attract our interest because of their continued high production volume and occurrence in aquatic biota, [10][11][12] osprey eggs, [13] human breast milk [14] and Arctic media (e.g. air, water and ice).…”
Section: Introductionmentioning
confidence: 99%
“…The bioaccumulation of contaminants such as DDTs (mainly as DDE), PCBs, dioxins, and heavy metals by fish represents a potentially significant risk to piscivorous wildlife [11,12,17]. Fish often comprise a substantial dietary portion of mammalian and avian species, and therefore represent a significant route of contaminant exposure.…”
Section: Resultsmentioning
confidence: 99%
“…For wildlife protection assessments, whole fish analyses are optimal. Because the susceptibility to contaminants varies among species, tissue residue guideline (toxicity threshold) for the protection of wildlife consumers of aquatic biota for DDTs was calculated as 0.15-3.0 µg/g and for PCBs 0.11-0.48 µg/g [17]. Although the concentrations of many persistent organochlorine chemical residues have declined over the past two decades, our and others authors' results indicate that contaminant residues still remain a risk to piscivorous wildlife at some sites [4,12,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…These concentrations are lower in all cases than the recommended maximum concentration limit by the Cuban standard of 1 mg.g x1 ww of As for fish consumption (NC-493, 2006) and in the same order of magnitude reported by other authors in freshwater fish. Hinck et al (2009) reported average concentration of 0.11 mg.g x1 ww for As in fish collected at 111 sites from some important river basins from the USA, with a maximum of 1.95 mg.g x1 ww for whole body. During a survey on fish fillets from Oak Ridge Reservation in Tennessee, USA, Burger and Campbell (2004) detected the presence of As in a concentration range between 0.085 and 0.140 mg.g x1 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in the Savannah River, USA, were found average levels of Se in fillet between 0.21 and 0.64 mg.g x1 ww for various species (Burger et al, 2001). Hinck et al (2009) studied piscivorous and benthivorous fish at 111 sites from US river basins and reported a mean of 0.59 mg.g x1 ww of Se in whole fish with a maximum value of 4.66 mg.g x1 ww. Lemly (1993) proposed an Se reference concentration of 4 mg.g x1 dw in whole body as threshold values for selenium toxicity involving reproductive failures and teratogenic deformities in young fish, although adults can survive and appear healthy.…”
Section: Resultsmentioning
confidence: 99%